Method for enriching and selectively leaching scandium in weathering crust type scandium ore

Through magnetic separation and roasting, the problems of scandium leaching in weathered shell scandium ore are solved, and efficient enrichment and selective leaching of scandium are achieved, which has good economic benefits and environmental friendliness.

CN119553103APending Publication Date: 2025-03-04INST OF GEOCHEMISTRY CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411736346.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The prior art has problems of no selectivity or environmental pollution when leaching scandium from weathered shell scandium ore, making it difficult to effectively enrich and selectively extract scandium.

Method used

Scandium is converted into soluble scandium sulfate and then selective leachate reaction with water to achieve selective leach of scandium.

Benefits of technology

The enrichment and selective leaching of scandium in weathered shell scandium ore has been achieved. The leaching rate of scandium after magnetic separation can reach 69.08%, and the leaching rate of iron is not higher than 8%, which has good selectivity and environmentally friendly characteristics.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a method for enriching and selectively leaching scandium in weathering crust type scandium ore, which belongs to the technical field of physical separation and chemical industry, and comprises the following steps: carrying out crushing and magnetic separation on the weathering crust type scandium ore to obtain iron and titanium magnetic components and scandium-rich non-magnetic components; and mixing the scandium-rich non-magnetic component with ferric sulfate, roasting, and adding water into the roasted clinker for leaching reaction to obtain scandium-containing leachate. According to the method, scandium in the weathering crust type scandium ore can be effectively enriched and leached, good potential economic benefits are achieved, and a technical route is provided for comprehensive resource utilization of the weathering crust type scandium ore.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of physical separation and chemical technology, and in particular relates to a method for enriching and selectively leaching scandium from a weathered shell-type scandium ore. Background Art

[0002] Scandium is one of the rare earth elements with excellent physical and chemical properties. It can be used as a doping additive to enhance the strength and ductility of aluminum alloys and reduce density, and is widely used in the aerospace field. It can enhance the conductivity of solid oxide fuel cells and reduce their operating temperature, and is widely used by battery manufacturers. It can also be added to lasers to enhance their power and be used in the military field. At present, more than 100 scandium-containing minerals have been discovered. However, the distribution of scandium in the earth's crust is relatively scattered, and it is difficult to recover. The grade of scandium-containing ores is low, which to a certain extent restricts its development and application. Scandium generally coexists in a homogeneous form in iron, nickel, titanium, tungsten, aluminum, zirconium and other ores. Resources containing 20-50ppm scandium are worth mining. Due to the high price of scandium (US$269 / g Sc), its wide application is limited. The global annual scandium consumption is only about 10-15 tons. China has rich weathering crust-type scandium resources, and the local scandium content has reached 304×10 -6 ppm. However, due to the complex mineral composition, close symbiotic relationship, fine embedded grain size, little difference in selectivity between valuable minerals and gangue minerals, and difficulty in separating valuable elements, weathered shell-type scandium resources have not yet been utilized.

[0003] The prior art has disclosed a variety of methods for leaching scandium from scandium-containing samples, mainly involving the following methods: (a) directly dissolving the scandium-containing sample with sulfuric acid, such as patent CN117285073A discloses a method for leaching scandium from Bayan Obo tailings with sulfuric acid. This method belongs to a high-temperature strong acid leaching process, and the leaching rate of scandium is only about 60% and there is no selectivity. Similarly, patent CN118668083A proposes to use hydrochloric acid to dissolve laterite scandium ore, and the leaching rate of scandium reaches about 75%, but there is also no selectivity. (b) leaching scandium after roasting the scandium-containing sample, such as patent CN114480887B discloses a method for selectively extracting scandium from laterite nickel ore using sulfuric acid roasting-water leaching. This method uses concentrated acid, the operation process is complicated and environmentally unfriendly. Patent CN114350958B discloses a method for simultaneously recovering iron, aluminum, scandium, vanadium, chromium, and sodium from red mud and enriching titanium. This method produces ammonia gas that pollutes the environment. In general, there are no patent reports on the leaching of scandium from weathered crust-type scandium ore. Existing scandium leaching technologies have problems such as non-selectivity or environmental pollution. Summary of the invention

[0004] In view of the above technical problems, the present invention proposes a method for enriching and selectively leaching scandium from weathered shell-type scandium ore.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A method for enriching and selectively leaching scandium in a weathered crust-type scandium ore comprises the following steps: crushing and magnetically separating the weathered crust-type scandium ore to obtain magnetic components of iron and titanium and non-magnetic components rich in scandium, mixing the non-magnetic components rich in scandium with ferric sulfate and then roasting them, adding water to the obtained roasted clinker to carry out a leaching reaction, and obtaining a leachate containing scandium.

[0007] Technical principle of the present invention: Weathering crust type scandium ore refers to the scandium deposit in the weathering crust overlying ultrabasic rock, basic rock or carbonate rock body. This type of scandium deposit is mainly formed by the weathering process, in which the scandium element is enriched during the weathering process. The present invention focuses on the fact that the scandium in the weathering crust type scandium ore is mainly present in goethite and montmorillonite. Generally, it is difficult to be selective for scandium when dissolving the weathering crust type scandium ore with inorganic acids (such as hydrochloric acid, sulfuric acid, etc.), that is, strong inorganic acids will dissolve iron, which is not conducive to the subsequent extraction and separation of scandium. The present invention utilizes the magnetic property of ilmenite in weathered shell-type scandium ore, firstly selects ilmenite by magnetic separation, and simultaneously enriches scandium in the tailings of magnetic separation, and then uses iron sulfate and the scandium ore after magnetic separation to roast to convert the scandium-containing mineral goethite in the sample into soluble scandium sulfate and iron sulfate, and then controls the roasting temperature to decompose the iron sulfate into water-insoluble iron oxide while the scandium sulfate does not decompose. Subsequently, the roasting product is leached with water, the scandium sulfate is dissolved in the water, and then the selective leaching of scandium is realized.

[0008] Furthermore, the current of the magnetic separation is 0.2-1A.

[0009] Furthermore, the mass ratio of the scandium-rich non-magnetic component to ferric sulfate is 1:(0.8-1).

[0010] Furthermore, the calcination conditions are: temperature 600-700° C., time 10-120 minutes.

[0011] Furthermore, the ratio of the roasted clinker to water is 1 g: 10 mL.

[0012] Furthermore, the conditions of the leaching reaction are: temperature 95° C., time 2.5 hours.

[0013] Weathering crust type scandium ore mainly contains iron (hydride) oxides (ilmenite, magnetite, hematite, goethite) and clay minerals (kaolinite, montmorillonite), as well as a small amount of quartz. The content of scandium is 82ppm, which can be extracted and recovered as a scandium resource. The present invention is aimed at the leaching of scandium in weathering crust type scandium ore, and proposes a method for enriching and selectively leaching scandium in weathering crust type scandium ore. The main steps are to magnetically separate the weathering crust type scandium ore to enrich scandium, and then mix iron sulfate with the scandium ore after magnetic separation in proportion and roast it to convert scandium into soluble scandium sulfate, and then use water to selectively leach the scandium in the roasted sample. After magnetic separation, the scandium in the magnetic tailings can be enriched from 82ppm to 92ppm, and the magnetic concentrate is mainly ilmenite, which can be used as an iron-titanium concentrate. The dissolution rate of scandium in the leaching solution is above 60%, and the dissolution rate of iron is not higher than 8%. The leaching solution can be used for extracting scandium.

[0014] Compared with the prior art, the present invention has the following advantages and technical effects:

[0015] Through the technical scheme of the present invention, scandium can be enriched and selectively leached from weathered shell-type scandium ore, and the scandium in the magnetic tailings after magnetic separation can be enriched from 82ppm to 92ppm. The magnetic concentrate is mainly ilmenite, which can be used as a resource, and the iron content in the leached sample is reduced. In the final leaching solution, the scandium leaching rate can reach up to 69.08%, while the iron leaching rate is not higher than 8%. The scandium-rich leaching solution can further separate and recover scandium, realizing the selective leaching of scandium in the weathered shell-type scandium ore.

[0016] The method of the invention has good scandium selection effect, and the obtained scandium-rich leaching solution is advantageous for subsequent extraction and separation of scandium, and is environmentally friendly. The invention can effectively enrich and leach scandium in weathered crust-type scandium ore, has good potential economic benefits, and provides a technical route for comprehensive resource utilization of weathered crust-type scandium ore. DETAILED DESCRIPTION

[0017] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0018] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0019] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0020] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0021] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0022] The invention provides a method for enriching and selectively leaching scandium in a weathered crust-type scandium ore, comprising the following steps: crushing and magnetically separating the weathered crust-type scandium ore to obtain iron and titanium magnetic components and a scandium-rich non-magnetic component, mixing the scandium-rich non-magnetic component with ferric sulfate and then roasting the mixture, adding water to the obtained roasted clinker to carry out a leaching reaction, and obtaining a scandium-containing leachate.

[0023] In some embodiments of the present invention, the current of the magnetic separation is 0.2-1 A. Exemplarily, in the following preferred embodiments of the present invention, the current of the magnetic separation can be selected to be 0.2 A. The particle size of the scandium-rich non-magnetic component obtained after magnetic separation is 0.074 mm.

[0024] The iron and titanium magnetic components obtained after magnetic separation can be used as ferro-titanium concentrate.

[0025] In some embodiments of the present invention, the mass ratio of the scandium-rich non-magnetic component to ferric sulfate is 1:(0.8-1). Exemplarily, in the following preferred embodiments of the present invention, the mass ratio of the scandium-rich non-magnetic component to ferric sulfate is 1:0.8, 1:1 or any range between the aforementioned ratios.

[0026] In some embodiments of the present invention, the calcination temperature is 600-700°C. For example, in the following preferred embodiments of the present invention, the calcination temperature is 600°C, 650°C, 700°C or any value between the aforementioned ranges. The calcination time is 10-120 minutes. For example, in the following preferred embodiments of the present invention, the calcination time is 10 minutes, 20 minutes, 40 minutes, 60 minutes, 120 minutes or any value between the aforementioned ranges.

[0027] In some embodiments of the present invention, the ratio of the roasted clinker to water is 1 g: 10 mL.

[0028] In some embodiments of the present invention, the conditions of the leaching reaction are: temperature 95° C., time 2.5 hours.

[0029] The method of the present invention can be used to leaching scandium from weathered shell-type scandium ore. The scandium leaching rate in the leaching solution can reach up to 69.08%, while the iron leaching rate is no higher than 8%, and has an obvious selectivity effect on scandium.

[0030] The raw materials used in the present invention are all purchased from the market.

[0031] The technical solution of the present invention is further illustrated by the following embodiments.

[0032] Example 1

[0033] (1) Dry the weathered shell-type scandium ore, weigh the weathered shell-type scandium ore after drying, and use a current of 0.2 A for magnetic separation. The Fe content of the original ore is 19.55%, the Ti content is 3.23%, and the Sc content is 81.9 ppm. After magnetic separation, the Fe content of the iron and titanium magnetic components is 45.3%, the Ti content is 6.83%, and the Sc content is 32 ppm. The Fe content of the magnetic separation tailings (non-magnetic components rich in scandium) is 12.80%, the Ti content is 1.98%, and the Sc content is 92 ppm;

[0034] (2) The magnetic tailings are dried and crushed to a particle size of 0.074 mm, and the magnetic tailings are mixed with iron sulfate in a mass ratio of 1:0.8, and roasted at 600°C for 60 minutes. The roasted clinker is mixed with water in a solid-liquid ratio of 1g:10mL and placed in a constant temperature water bath oscillator for reaction at 95°C for 2.5 hours to obtain a scandium-containing leaching solution.

[0035] After testing, the scandium leaching rate was 61.85% and the iron leaching rate was 4.61%.

[0036] Example 2

[0037] (1) Same as step (1) of Example 1;

[0038] (2) The magnetic tailings are dried and crushed to a particle size of 0.074 mm, mixed with ferric sulfate in a mass ratio of 1:1, roasted at 600°C for 60 minutes, and the roasted clinker is mixed with water in a solid-liquid ratio of 1g:10mL and placed in a constant temperature water bath oscillator for reaction at 95°C for 2.5 hours to obtain a scandium-containing leaching solution.

[0039] After testing, the scandium leaching rate was 66.67% and the iron leaching rate was 7.42%.

[0040] Example 3

[0041] (1) Same as step (1) of Example 1;

[0042] (2) The magnetic tailings are dried and crushed to a particle size of 0.074 mm, and the magnetic tailings are mixed with iron sulfate in a mass ratio of 1:0.8, and roasted at 600°C for 120 minutes. The roasted clinker is mixed with water in a solid-liquid ratio of 1g:10mL and placed in a constant temperature water bath oscillator for reaction at 95°C for 2.5 hours to obtain a scandium-containing leaching solution.

[0043] After testing, the scandium leaching rate was 61.85% and the iron leaching rate was 4.06%.

[0044] Example 4

[0045] (1) Same as step (1) of Example 1;

[0046] (2) The magnetic tailings are dried and crushed to a particle size of 0.074 mm, and the magnetic tailings are mixed with iron sulfate in a mass ratio of 1:0.8, and roasted at 650°C for 20 minutes. The roasted clinker is mixed with water in a solid-liquid ratio of 1g:10mL and placed in a constant temperature water bath oscillator for reaction at 95°C for 2.5 hours to obtain a scandium-containing leaching solution.

[0047] After testing, the scandium leaching rate was 65.06% and the iron leaching rate was 3.59%.

[0048] Example 5

[0049] (1) Same as step (1) of Example 1;

[0050] (2) The magnetic tailings are dried and crushed to a particle size of 0.074 mm, and the magnetic tailings are mixed with iron sulfate in a mass ratio of 1:1, and roasted at 650°C for 40 minutes. The roasted clinker is mixed with water in a solid-liquid ratio of 1g:10mL and placed in a constant temperature water bath oscillator for reaction at 95°C for 2.5 hours to obtain a scandium-containing leaching solution.

[0051] After testing, the scandium leaching rate was 68.67% and the iron leaching rate was 6.17%.

[0052] Example 6

[0053] (1) Same as step (1) of Example 1;

[0054] (2) The magnetic tailings are dried and crushed to a particle size of 0.074 mm, and the magnetic tailings are mixed with iron sulfate in a mass ratio of 1:0.8, and roasted at 700°C for 10 minutes. The roasted clinker is mixed with water in a solid-liquid ratio of 1g:10mL and placed in a constant temperature water bath oscillator for reaction at 95°C for 2.5 hours to obtain a scandium-containing leaching solution.

[0055] After testing, the scandium leaching rate was 66.27% and the iron leaching rate was 4.49%.

[0056] Example 7

[0057] (1) Same as step (1) of Example 1;

[0058] (2) The magnetic tailings are dried and crushed to a particle size of 0.074 mm, and the magnetic tailings are mixed with iron sulfate in a mass ratio of 1:1, and roasted at 700°C for 10 minutes. The roasted clinker is mixed with water in a solid-liquid ratio of 1g:10mL and placed in a constant temperature water bath oscillator for reaction at 95°C for 2.5 hours to obtain a scandium-containing leaching solution.

[0059] After testing, the scandium leaching rate was 69.08% and the iron leaching rate was 7.13%.

[0060] Comparative Example 1

[0061] (1) Same as step (1) of Example 1;

[0062] (2) The magnetic tailings are dried and crushed to a particle size of 0.074 mm, and the magnetic tailings are mixed with iron sulfate in a mass ratio of 1:1, and roasted at 700°C for 10 minutes. The roasted clinker is mixed with water in a solid-liquid ratio of 1g:10mL and placed in a constant temperature water bath oscillator for reaction at 30°C for 2.5 hours to obtain a scandium-containing leaching solution.

[0063] After testing, the scandium leaching rate was 53.01% and the iron leaching rate was 33.48%.

[0064] Comparative Example 2

[0065] (1) Same as step (1) of Example 1;

[0066] (2) The magnetic tailings are dried and crushed to a particle size of 0.074 mm, mixed with ferric sulfate in a mass ratio of 1:1, and roasted at 700°C for 10 minutes. The roasted clinker is mixed with water in a solid-liquid ratio of 1g:10mL and placed in a constant temperature water bath oscillator for reaction at 60°C for 2.5 hours to obtain a scandium-containing leaching solution.

[0067] After testing, the scandium leaching rate was 61.45% and the iron leaching rate was 25.01%.

[0068] It can be seen from Comparative Examples 1-2 that too low a leaching temperature is not conducive to the leaching of scandium, but will increase the leaching rate of iron, which is obviously not selective.

[0069] Comparative Example 3

[0070] The weathered shell-type scandium ore is dried, and the Fe content, Ti content, and Sc content of the original ore are 19.55%, 3.23%, 81.9 ppm, and the particle size is 0.074 mm. The weathered shell-type scandium ore and iron sulfate are mixed in a mass ratio of 1:1, and roasted at 600°C for 60 minutes. The roasted clinker is mixed with water in a solid-liquid ratio of 1g:10mL and placed in a constant temperature water bath oscillator to react at 95°C for 2.5 hours to obtain a scandium-containing leaching solution.

[0071] According to the test, the leaching rate of scandium is 67.90% and the leaching rate of iron is 14.20%.

[0072] It can be seen from Comparative Example 3 that the iron concentration in the leachate is higher when the sample without magnetic separation is leached, indicating that the pretreatment of magnetic separation reduces the iron content in the sample and thus reduces the iron concentration in the leachate, which is beneficial to the selective leaching of scandium.

[0073] Comparative Example 4

[0074] Same as Example 7, except that the calcination temperature in step (2) is 500°C.

[0075] After testing, the scandium leaching rate was 53.15% and the iron leaching rate was 17.49%.

[0076] Comparative Example 5

[0077] Same as Example 7, except that the mass of iron sulfate in step (2) is replaced by ammonium sulfate.

[0078] According to the test, the leaching rate of scandium is 75.10%, and the leaching rate of iron is 19.10%. The selectivity for scandium is not good.

[0079] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for enriching and selectively leaching scandium from a weathered crust-type scandium ore, characterized in that: The following steps are involved: The weathered shell-type scandium ore is crushed and magnetically separated to obtain iron and titanium magnetic components and scandium-rich non-magnetic components. The scandium-rich non-magnetic components are mixed with ferric sulfate and then roasted. Water is added to the obtained roasted clinker for leaching reaction to obtain a scandium-containing leachate.

2. The method for enriching and selectively leaching scandium from weathered shell-type scandium ore according to claim 1, characterized in that: The current of the magnetic separation is 0.2-1A.

3. The method for enriching and selectively leaching scandium from weathered shell-type scandium ore according to claim 1, characterized in that: The mass ratio of the scandium-rich non-magnetic component to ferric sulfate is 1:(0.8-1).

4. The method for enriching and selectively leaching scandium from weathered shell-type scandium ore according to claim 3, characterized in that: The mass ratio of the scandium-rich non-magnetic component to ferric sulfate is 1:

1.

5. The method for enriching and selectively leaching scandium from weathered shell-type scandium ore according to claim 1, characterized in that: The calcination conditions are: temperature 600-700° C., time 10-120 minutes.

6. The method for enriching and selectively leaching scandium from weathered shell-type scandium ore according to claim 5, characterized in that: The calcination conditions are: temperature 700° C., time 10 minutes.

7. The method for enriching and selectively leaching scandium from weathered shell-type scandium ore according to claim 1, characterized in that: The usage ratio of the roasted clinker to water is 1g:10mL.

8. The method for enriching and selectively leaching scandium from weathered shell-type scandium ore according to claim 1, characterized in that: The conditions of the leaching reaction are: temperature 95° C., time 2.5 hours.

Citation Information

Patent Citations

  • A method for simultaneously recovering iron, aluminum, scandium, vanadium, chromium and sodium from red mud and enriching titanium

    CN114350958B